If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -3t = 6 Solving 18 + -3t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -3t = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -3t = 6 + -18 -3t = 6 + -18 Combine like terms: 6 + -18 = -12 -3t = -12 Divide each side by '-3'. t = 4 Simplifying t = 4
| 4(1+2a)=-6a(a-3) | | 5y-3=7y | | 7+4n=23 | | 4x-3=2x+38 | | 220+220(0.105)-220(0.1)=x | | 5+5x-6=9 | | 8xn=51 | | 2x*5=4x+13 | | 4(-3k+8)=-6k+2(5k+8) | | Ix-4I=-3 | | 3n+6=16 | | F(x)=cos(pi+x) | | 3y+2=7y+10 | | g(z)=Cos(pi+g) | | 4y+2x=13.50 | | .77=In(y) | | 46=-5(m+3)-7(m-7) | | 0.77=ln(y) | | 0.5x-4=7-x | | 7+2[a-3]=-9 | | -8a+15=-105 | | 4x+2y=13.50 | | H-(-7)=12 | | 4x+2x=13.50 | | -6(a+8)+6(1-8)=-78 | | 7x-5=5x+8 | | -7x-4-4x=9x+4x | | (x^2+10+25)-5=25 | | 2[a-4]+15=13 | | 1x^2=0 | | 5x+2x-5=30 | | 10+3x-4=18 |